Operation Dumbo drop [videorecording (DVD)] - Wincer, Simon; Glover, Danny; Liotta, Ray; Leary, Denis (Disney DVD., 2002)
A group of Green Berets are faced with a military maneuver to transport an elephant across 200 miles of rivers, mountains and canyons to a remote jungle village.